2009
DOI: 10.1051/0004-6361/200811460
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of non-radial pulsations in the spectroscopic binary Herbig Ae star RS Chamaeleontis

Abstract: Context. To understand the origin of stellar activity in pre-main sequence Herbig Ae/Be stars and to get a deeper insight in the interior of these enigmatic stars, the pulsational instability strip of Palla and Marconi is investigated. In this article we present a first discovery of non radial pulsations in the Herbig Ae spectroscopic binary star RS Cha. Aims. The goal of the present work is to detect for the first time directly by spectrographic means non-radial pulsations in a Herbig Ae star and to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…A weighted combination of the nightly F2D spectra can be seen in Fig. 5 (see Böhm et al 2009, for details of the method) and our results confirm the presence of low-degree non-radial pulsations: a peak at the dominant frequency F 1 is clearly seen with an apparentm of between 2 and 4 indicating a degree of between 0 and 2. Moreover, as can be seen in Table 2.3 of Kennelly (1994) (or in simulations with available online-NRP simulators), the symmetric pattern of the dynamical residual profile as seen in Fig.…”
Section: Mode Identification With the Fourier 2d Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…A weighted combination of the nightly F2D spectra can be seen in Fig. 5 (see Böhm et al 2009, for details of the method) and our results confirm the presence of low-degree non-radial pulsations: a peak at the dominant frequency F 1 is clearly seen with an apparentm of between 2 and 4 indicating a degree of between 0 and 2. Moreover, as can be seen in Table 2.3 of Kennelly (1994) (or in simulations with available online-NRP simulators), the symmetric pattern of the dynamical residual profile as seen in Fig.…”
Section: Mode Identification With the Fourier 2d Methodssupporting
confidence: 77%
“…Most of them have been studied in photometry, but only very few in spectroscopy (e.g. Böhm et al 2004Böhm et al , 2009). However, owing to cancellation effects, only modes of low degree are detected in photometry or radial velocity curves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their asteroseismological properties allow constraints to be placed on various PMS physical parameters, such as luminosity, mass and effective temperature, as well as on the internal structure, which is different from that of more evolved stars of the same mass. Good examples of known PMS δ Scuti stars are the spectroscopic binary system RS Chamaeleontis (Böhm et al 2009), V351 Ori (Ripepi et al 2003) and IP Per (Ripepi et al 2006). However, the asteroseismological study of some of the δ Scuti PMS stars found here is still in progress and is deferred to another paper (Ripepi et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…Still, they report 22.079 d −1 as the most prominent variation for the primary component. Böhm et al (2009) observed RS Cha for 14 nights with the high-resolution echelle spectrograph Hercules at the Mt John telescope in New Zealand. They report the first clear detection of pulsation frequencies, both for the primary and secondary component.…”
Section: Pulsationsmentioning
confidence: 99%